Experiences With Repair Of Ulnar Nerve Injuries (A Study of Twelve Cases) - Siti Roy Chowdhury; R. N. Roy (Indian Journal of Plastic Surgery)
The quality of recovery after nerve suture in this series appears to be better in younger patients.